Evaluation of Urban Water System Development from the Perspective of Space - XIE Qianwen; LIU Jiangtao; WEI Jie; REN Dawei (Renmin Zhujiang)
To adapt to the reform of spatial planning in the new era,this study evaluates the urban water system from the new perspective of space and lays the foundation for the future use of spatial means to realize the optimization and sustainable development of urban water system functions.Taking Shenzhen as an example,this paper divides its urban water system space into four types,namely,resource ecology space,engineering facility space,water-city integrated space,and safety risk space,and evaluates them from the dimensions of the total space,composition and layout,system carrying capacity,and space quality.The results indicate that the space occupancy rate of the water system is generally low,and the local water resources and the carrying capacity of the water environment are limited,which are vulnerable to multiple disasters of floods and surges.The potential risk areas are mainly distributed in densely populated areas and industry-intensive areas.The spatial service quality of the water system has great potential for improvement considering the low biodiversity of rivers and lakes,the insufficient attraction of waterfront space,and a low proportion of the complex utilization of facility space.